MATHEMATICS CLASSROOM ACTIVITIES BASED ON SOME TOPICS IN GRAPH THEORY TO DEVELOP CRITICAL THINKING OF PRIMARY AND SECONDARY SCHOOL STUDENTS - Santoso, Eko Budi (International Journal of Indonesian Education and Teaching (IJIET), 2018)
In Indonesia, graph theory is not part of the Mathematics education curriculum at primary or secondary school Curriculum. Most students learn graph theory in university, especially those who takes major in Mathematics or Computer Science. This paper is a theoretical study in Mathematics Education which proposes some Mathematics classroom activities based on some concepts in graph theory to develop critical thinking for high school students as well as grade school. Some concepts in graph theory, such as vertex coloring and domination set can be used in primary and secondary schools to develop critical thinking of the students. These activities should be fun for the students since the teacher may use it as a game in the classroom.Â DOI :Â https://doi.org/10.24071/ijiet.2018.020207